Total Phenolic, Total Flavonoid, Tannin Content, and Antioxidant Capacity of Halimium halimifolium (Cistaceae) - Ahlem Rebaya, Souad Igueld Belghith, Béatrice Baghdikian, Valérie Mahiou Leddet, Fathi Mabrouki, Evelyne Olivier, Jamila kalthoum Cherif & , Malika Trabelsi Ayadi (Journal of Applied Pharmaceutical Science, 2015)
This study was carried out to evaluate the phytochemical constituents and antioxidant potential of the leaves and flowers extracts of Halimium halimifolium in order to validate the medicinal potential of this herb. The antioxidant activity of alcoholic and aqueous extracts was evaluated using 2, 2-diphenyl-l-picrylhydrazyl (DPPH), 2, 2’-azinobis- (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) and ferric reducing antioxidant power (FRAP) assays. The total polyphenol, flavonoid and tannin content were determined according respectively to Folin-Ciocalteu method, Zhishen method and Broadhurst method. The leaves of H. halimifolium had greater antioxidant activity than flowers by DPPH and ABTS assays. The ethanol extract of the leaves exhibited the better antioxidant activity by DPPH assay (IC50 = 1.19 µg.mL-1), the n-butanol by ABTS assays (IC50 = 1.73µg.mL-1). As opposed to FRAP method the flowers had greater antioxidant activity as leaves. Ethyl acetate extract exhibited better antioxidant activity (IC50 = 15.5 mmol Fe2+.g-1). The obtained results showed that the extracting solvent significantly influenced the antioxidant property estimations of Halimium halimifolium. The ethanol is a recommended solvent for extracting antioxidants from this plant. The antioxidant activity determined by DPPH, ABTS and FRAP demonstrated a linear relationship with their polyphenols, flavonoids and tannins content.
Keywords: Halimium halimifolium, Cistaceae, antioxidant activity, polyphenols.